2013
DOI: 10.1007/s12105-012-0418-8
|View full text |Cite
|
Sign up to set email alerts
|

Fibromatosis Arising in Association with Neuromuscular Hamartoma of the Mandible

Abstract: Aggressive fibromatosis is a benign but locally-aggressive tumor, which most often affects the muscles of the shoulder, the pelvic girdle, and the thigh. It usually affects adolescents and young adults. Desmoplastic fibroma, considered the bone counterpart of soft tissue fibromatosis, is a rare tumor that usually affects the metaphyseal or diaphyseal portions of long bones or, less commonly, the jaw. Neuromuscular hamartoma, a rare developmental lesion composed of mature elements of both striated muscle and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…have reported immunopositivity for beta-catenin in DF cases. [ 17 18 19 ] Similar to one of our cases, Hauben et al , Wood et al . and Kahraman et al .…”
Section: Discussionsupporting
confidence: 87%
“…have reported immunopositivity for beta-catenin in DF cases. [ 17 18 19 ] Similar to one of our cases, Hauben et al , Wood et al . and Kahraman et al .…”
Section: Discussionsupporting
confidence: 87%
“…In 2005, Hauben et al [10] reported two cases of mandibular DFs that stained positively with b-catenin; however only one demonstrated nuclear positivity and thereby deemed true positive labeling. Multiple cases of gnathic DF have since been shown to be reactive to b-catenin [10,17,18]. Most recently, Gondak et al [19] reported a maxillary lesion with negative reactivity to b-catenin (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“… 20 21 Desmoid-type fibromatoses and adenocarcinoma have positive results for β-catenin. 20 Multiple cases of desmoplastic fibromas of the jaw bones have been reactive to β-catenin, 22 23 24 while some have not been. 12 22 25 …”
Section: Discussionmentioning
confidence: 99%